2005
DOI: 10.1111/j.0105-2896.2005.00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Bruton's tyrosine kinase: cell biology, sequence conservation, mutation spectrum, siRNA modifications, and expression profiling

Abstract: Bruton's tyrosine kinase (Btk) is encoded by the gene that when mutated causes the primary immunodeficiency disease X-linked agammaglobulinemia (XLA) in humans and X-linked immunodeficiency (Xid) in mice. Btk is a member of the Tec family of protein tyrosine kinases (PTKs) and plays a vital, but diverse, modulatory role in many cellular processes. Mutations affecting Btk block B-lymphocyte development. Btk is conserved among species, and in this review, we present the sequence of the full-length rat Btk and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
156
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 179 publications
(170 citation statements)
references
References 109 publications
(126 reference statements)
3
156
1
2
Order By: Relevance
“…According to many recent studies, no simple pattern of genotype-phenotype correlations has been established in patients with XLA [Broides et al, 2006;Lindvall et al, 2005;López-Granados et al, 2005;Vihinen and Durandy, 2006]. Highly significant differences appear in the frequency of missense mutations as compared to frameshifts, and sites that seem to be essentially resistant to substitutions were previously reported by us [Lindvall et al, 2005].…”
Section: Mutation Statisticsmentioning
confidence: 90%
See 4 more Smart Citations
“…According to many recent studies, no simple pattern of genotype-phenotype correlations has been established in patients with XLA [Broides et al, 2006;Lindvall et al, 2005;López-Granados et al, 2005;Vihinen and Durandy, 2006]. Highly significant differences appear in the frequency of missense mutations as compared to frameshifts, and sites that seem to be essentially resistant to substitutions were previously reported by us [Lindvall et al, 2005].…”
Section: Mutation Statisticsmentioning
confidence: 90%
“…This is a highly significant difference, po0.0001, suggesting that there is a genotype-phenotype correlation. We previously reported that missense mutations as compared to frameshift mutations (including nonsense) only affect a limited number of amino acid positions in the BTK gene, in analogy with the F9 gene, which encodes a coagulation factor [Lindvall et al, 2005]. Moreover, we found that for TGA codons, which when mutated either form stop codons, or result in amino acid substitutions, residues R13 as well as R255 were exclusively mutated to stop codons (po0.001).…”
Section: Mutation Statisticsmentioning
confidence: 93%
See 3 more Smart Citations